A modified Cuk DC-DC converter for DC microgrid systems - Andriazis Dahono; Arwindra Rizqiawan; Pekik Argo Dahono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
A new efficient step-updirect current-direct current (DC-DC) power converter that is suitable for DC microgrid systems is proposed in this paper. The proposed step-up DC-DC converter is derived from the conventional Cuk DC-DC power converter. Output voltage analysis that is useful to predict the conduction losses is presented. It is shown that the proposed step-up DC-DC converter is more efficient than the conventional DC-DC boost power converter. Current ripple analysis that is useful to determine the required inductors and capacitors is also presented. Experimental results are included to show the validity of the proposed step-up DC-DC power converter.